Some problems of socio-cultural research in mathematics teaching and learning - Lerman, Stephen (NOMAD Nordic Studies in Mathematics Education, 2000)
In the spirit of the conference, this article is not to argue for a socio-cultural perspective. I have been working in this area for close on a decade now and although I sometimes engage in discussions about theoretical perspectives (see Lerman, 1996; 2000) the intention of this paper is somewhat different. Instead I will first summarise some of what I consider the key notions of socio-cultural theory for education in general terms. I will then describe some of the aspects of a socio-cultural perspective on mathematics teaching and learning with which currently I struggle in my work.